Hepatitis B virus infection in northern Uganda: Impact of pentavalent hepatitis B vaccination. Issue 46 (17th November 2015) - Teshale, Eyasu H.; Kamili, Saleem; Drobeniuc, Jan; Denniston, Maxine; Bakamutamaho, Barnabas; Downing, Robert
Abstract: Chronic hepatitis B virus infection (CHBI) is effectively prevented by vaccination starting at birth. Beginning in 2002 Uganda adopted a policy of providing the pentavalent hepatitis B vaccine starting at 6 weeks of age. However, there is concern that this delay may leave the infant vulnerable to infection during the first 6 weeks of life. We assessed whether vaccination at 6 weeks was an effective strategy by HBV serologic study. Of 656 persons tested for HBV, 9.4% were chronically infected; among children aged 5–9 years the prevalence was 7.6%. Of all tested, 73 were born (i.e., aged ≤4 years) after the introduction of the pentavalent vaccine; none were infected with HBV ( p  = 0.003). In this study, vaccination with the pentavalent vaccine at 6 weeks did not result in CHBI, but rather provides an opportunity to prevent mother-to-infant transmission of HBV infection where there is no access to birth-dose vaccine.